Peru-China international trade and its effect on inclusive economic growth in Peru 2000-2019 - Angulo-Bustinza, Harold D. (2022)
From 2000 to 2019, trade between the People's Republic of China and the Republic of Peru grew at an average annual rate of 22%, however, income and wealth inequality in Peru remained the same. The aim of this study is to understand the effect of trade between Peru and China on the inclusive economic growth of Peru from 2000 to 2019. The method used was the correlation of variables, and a linear regression between Peru and China trade and several indicators of inclusive economic growth in the Peruvian economy was performed using the Ordinary Least Squares model. The results suggest that there is sufficient statistical evidence to support that inclusive economic growth may depend on increased trade between Peru and China; the study show that if trade growth between Peru and China fluctuates by $1 million per year, labor income will increase by $10.3 per capita in the Economically Active Population (EAP). Moreover, for every 1% increase in trade between Peru and China, GDP per capita increases by 0.1057% and labor productivity increases by 0.0681740%. The variables poverty, vulnerable employment, GINI index and life expectancy at birth were not significant factors.